The relationship between corporate governance and firm's capital structure Malaysian evidence - Muhammad Ashraf, Anuar (2015)
This study examines the relationships between corporate governance mechanisms (bankers on board, family-owned company, CEO duality, board size, and board composition), including control variables (firm size, firm age and firm‟s profitability) with capital structure (debt-equity ratio) of listed companies in Malaysia. This study uses data from 60 largest listed companies, based on their market capitalization, from all sectors in Malaysia except financial institution and insurance companies. The time period covered is from 2000 to 2004, that is, after the announcement of the Malaysian Code of Corporate Governance in 2000. This study finds positive relationships between capital structure and bankers on board, family-owned company, board composition, and firm size. The relationships on family-owned company and firm size are significant, with both have strongly influencing the firms‟ capital structure. Profitability has a negative relationship. Board size and firm age both have negative, but significant relationships with the firms‟ capital structure. Generally, the existing literature on the relationships between corporate governance and capital structure has supported the findings of this study